Structural damage assessment of reinforced concrete buildings in Adiyaman after Kahramanmaras, (Türkiye) Earthquakes on 6 February 2023 - Ince, Ozan (Pergamon-Elsevier Science Ltd, 2024)
Two destructive earthquakes (Mw: 7.7 and Mw: 7.6) occurred in Kahramanmaras,, Turkiye, on February 6, 2023. The epicenters of these two earthquakes were very close to each other (approximately 90 km apart), and both took place on the same day. The first earthquake occured at 04:17 local time with a magnitude of 7.7 and a depth of 8.6 km, while the second earthquake occurred at 13:24 local time with a magnitude of 7.6 and a depth of 7.0 km. These two earthquakes caused extensive damage, particularly in 11 provinces, with Adiyaman being one of the hardest-hit areas. Most buildings in Adiyaman were severely affected or collapsed as a result of the earthquakes. Reports indicate that over 35,000 buildings collapsed in the aftermath. Furthermore, between February 6, 2023, and May 6, 2023, more than 30,000 aftershocks, ranging in magnitude from 0.2 to 6.6, were recorded. In this study, earthquake damages in reinforced concrete buildings in Adiyaman province were evaluated. The causes of damages in reinforced concrete buildings were evaluated in terms of material quality, design of building and reinforcement details. Field observations are also provided, along with accompanying pictures. The earthquake regulations in Turkiye, established in 1975, 1998, 2007, and 2018, which apply to a significant portion of the country's buildings, are discussed. An evaluation was conducted to assess whether the damaged buildings complied with the earthquake regulations in Turkiye. Field observations revealed that the earthquake regulations, particularly in relation to reinforcement details, were overlooked. In addition, designers should avoid design mistakes such as to make discontinuous of frames, to place most of vertical element strong axis in one direction, insufficient support condition of stairs and adjacent building effects.
Keywords: Earthquake; Reinforced concrete buildings; Reinforcement details; Structural failure; Kahramanmaras , earthquakes; Adiyaman